FROM THE FIRST TO THE FOURTH INDUSTRIAL REVOLUTION - Michalski, Marek (Człowiek w cyberprzestrzeni, 2020)
In 1769 James Watt, Scottish engineer received patent protection for his steam engine model. Like many other engineers he had been testing the atmospheric pressure and water vapour pressure already since the 17th century. The aim was to create a new source of propulsion for a variety of situations to replace muscle and labour for both humans and animals, or water power to dry wetlands, supply water to cities and homes, pump water out of mines, extinguish fires, and turn mill wheels. Already in early 18 century, the so-called Savery machine established its place at homes and other places as gardens in and around London, before being ousted by Newcomen machine. The latter with time became quite popular not only in England, but also in mainland Europe . Already in 1733, a company was founded to operate the Newcomen machine, in universal use in England by 1860s. However, steady work on the improvement of the machine was underway to reduce energy loss – so significant that fuel costs far outweighed the benefits.